Students’ Motivation Level in Gamification of Accounting Teaching and Learning – A Case of ‘Accounting on the Block’ - Jamaluddin, Junaidah; Mahali, Mahathir; Mohd Din, Norlaila; Nias Ahmad, Mohamad Azmi; Mohamad Fadzillah, Nur Syazwani; Abdul Jabar, Faizan (UiTM Press, 2020)
Learning accounting can be very challenging for most students. Students are not only expected to demonstrate a proficiency in accounting process, they must also demonstrate a depth of knowledge and understanding of accounting concepts and fundamentals. In most accounting courses, educators depend on the textbook or power point slides to give lectures and illustrate all the workings on the black/whiteboard while students are listening passively or busy taking notes. Lack of attraction and engagement in the conventional way of accounting teaching and learning may lead to difficulty in understanding basic accounting concepts and overall accounting process, thereby demotivating students to learn accounting. Alternatively, gamification of teaching and learning may provide a useful technique to enhance students’ engagement and motivation. For this reason, the authors have proposed a gamification technique, known as “Accounting on the Block” (AOTB), which is an accounting board game to teach Published Financial Statements for accounting students at diploma level. While numerous studies have been conducted to evaluate students’ motivation level in digital game-based learning, there are relatively few studies that address students’ motivation level when using physical games, such as board games. To shed light in this area, a case study was conducted on 50 accounting students who were experimented with the AOTB board game. The Instructional Materials Motivation Survey (IMMS) instrument was applied to measure students’ motivation level. The results revealed that most students’ motivation levels were positive and they were satisfied with the use of AOTB board game in their learning. However, students also expected improvements in some aspects of the game.